Satisfação conjugal e bem- estar subjetivo: Contribuições dos valores, traços de personalidade e atributos pessoais - Gomes, Ana Isabel Araújo Silva de Brito (2016)
The marital satisfaction and subjective well-being of partners are important variables to comprehend the dynamic of intimate relationships. Therefore, identifying their correlates is fundamental. In this direction, this thesis had the goal to know how human values, personality traits and real attributes of the respondent are correlated with their marital satisfaction and subjective well-being. Four empirical studies were developed. Study 1 aimed at elaborating the Self-perception of Attributes in Intimate Relationships Scale (SPAIRS), counting on the participation of 218 university students with mean age of 26 years old (51.4% female), who responded the scale and demographic questions. Results indicated a four-factor structure, and the indices of internal consistency (Cronbach’s alpha, a) were as it follows: .47 (traditional), .50 (successful), .84 (caring) e .86 (athletic). Study 2 aimed at knowing the psychometrical parameters of the SPAIRS with an independent sample, gathering 213 university students with mean age of 23 years old (51% female), who responded the scale and demographic questions. A model with the two factors of interest was tested [athletic (a = .77) and successful (a = .56)], proving to be adequate (?²/gl = 2.54, GFI = .94 and RMSEA = .08). Study 3 aimed at knowing how human values, personality traits and personal attributes are correlated with the marital satisfaction and the subjective well-being of the respondents. Participants were 416 people, being 208 heterosexual couples in a stable relationship (66.7%) or engaged (33.3%), the women with mean age of 24 years, and the men with mean age of 26 years. They responded the SPPAIRS, the Basic Values Survey, the Big Five Inventory, the Marital Satisfaction Scale, the Subjective Happiness Scale, the Positivity Scale, the Satisfaction with Life Scale, and the Positive and Negative Affect Scale, besides demographic questions. Results indicated that marital satisfaction was higher for men when compared to women, being more directly and indistinctively correlated to suprapersonal values. In the case of the subjective well-being, men and women did not differ, but this variable was positively correlated to the values of promotion and interaction, respectively. The trait of openness to experience, independently of the gender of the respondent, was the one that correlated directly the most with marital satisfaction and subjective well-being. At last, regarding the attributes, successful was correlated with marital satisfaction for men, and specially with subjective wellbeing. Study 4 aimed at replicating the finding of the previous study, counting on 480 people, 240 married heterosexual couples (85.7%) or in a stable relationship (14.3%), and the mean ages were 35 and 38 years for women and men, respectively. Consistently, marital satisfaction was higher for men, and was correlated with suprapersonal values; the correlation between subjective well-being and values of promotion for men and interactive for women. The traits of openness to experience and extroversion were the ones that correlated the most with marital satisfaction and subjective well-being. Finally, the attribute successful was the one that correlated the most with marital satisfaction and subjective well-being. In conclusion, the contributions of human values, personality traits and personal attributes as correlates of marital satisfaction and subjective well-being seem evident. These findings are discussed according to the literature, admitting the limitations of the studies, and suggesting others that might be developed in the future.